Boreal forest tree growth and sap flow after a low-severity wildfire - Stefan Doerr (Agricultural and Forest Meteorology, 2024)
Boreal forests are exposed to larger and more frequent fires due to climate change, with significant consequences for their carbon and water balances. Low-severity fires (trees charred but surviving) are the most common fire regime in the Eurasian boreal forest, but we still lack understanding on how they impact tree functioning. This study focused on the dynamics of tree transpiration and stem growth of Pinus sylvestris in central Sweden after a large wildfire in 2018. We compared a stand impacted by low-severity fire (LM) with an unburnt stand (UM), over three years following the fire (2020–2022). We found that transpiration was on average lower and more variable within the stand at LM compared to UM. LM also had consistently lower stem growth compared to UM, resulting in larger accumulated growth for the unburnt site in the second to fourth year after the fire. Our results highlight the complex effects of low-severity fire on tree water cycling, with both direct (damage to tree xylem and roots) and indirect fire impacts (due to loss of understory vegetation and changes in soil properties). Trees affected by low-severity fire also exhibited reduced resilience to water shortages. Considering the expected increase in frequency of droughts and forest fires at higher northern latitudes, such indirect fire impacts may put additional pressure on the boreal forest.